2014
DOI: 10.1182/blood.v124.21.4049.4049
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction in Pediatric Thalassemia Major Patients and Evaluation of Urine NGAL Levels in Thalassemia

Abstract: Aim: There are limited studies on renal involvement in beta-thalassemia patients. The aim of the present study was to investigate renal dysfunctions in pediatric patients with transfusion dependent beta thalassemia major (TD-βTM), using both conventional and early markers of glomerular and tubular dysfunctions and corralate findings to iron chelation therapy, deferasirox. Neutrofil-gelatinase associated lipocalin (NGAL) is an emerging biomarker in early diagnosis of acute kidney injury and also elevated urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similarly, several studies reported that β-thalassemia major patients had higher levels of urinary NGAL compared to control (Roudkenar et al 2008;Ozek et al 2014;Şen et al 2015). The principal finding of the current study is that patients with β-thalassemia major and intermedia had considerably elevated levels of serum NGAL compared to control independent of age and sex.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, several studies reported that β-thalassemia major patients had higher levels of urinary NGAL compared to control (Roudkenar et al 2008;Ozek et al 2014;Şen et al 2015). The principal finding of the current study is that patients with β-thalassemia major and intermedia had considerably elevated levels of serum NGAL compared to control independent of age and sex.…”
Section: Discussionsupporting
confidence: 69%
“…2. β-thalassemia and the nephron (14) renal impairment in cases of sepsis, administration of nephrotoxic drugs, contrast-induced nephropathy, urinary infections, glomerulonephritis, diabetic nephropathy, lupus nephropathy, and transfusiondependent anemias (18,19,20). Velat Sen et al (2015) indicate NGAL as a potential marker in screening or renal dysfunctions in patients with β-TM (4).…”
Section: Introductionmentioning
confidence: 99%